Impact of Shift Work on Excessive Daytime Sleepiness among Healthcare Shift Workers - Erinka Harlynadia; Ray Wagiu Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2023)
Background: The circadian rhythm can disturb caused by the shift work system, that effect leading to daily sleepiness, and a higher risk of serious health problems. Many healthcare workers are shift workers. Being drowsy condition when one is not expected to be drowsy is called Excessive daytime sleepiness (EDS). EDS is associated with poor sleep hygiene, workspace errors, a lack of productivity, and lack of concentration which are significant safety concerns and a higher risk of occupational accidents among nightshift workers. This study aims to review the original studies on the association of shift work with excessive daytime sleepiness among healthcare shift workers. Methods:  This article is a literature review consisting of journal articles. Articles were searched in the following databases PubMed, Scientific Scholar, Google Scholar, and EBSCO. The search terms used were ‘shift work’. ‘Excessive daytime sleepiness’ and Limitations included ‘English language’, ‘published between 2013-2023’, and ‘shift workers’.Results: Based on eleven articles that were analyzed, shift work and excessive daytime sleepiness are directly related to each other among shift workers. There are factors that cause EDS including lack of sleep duration and sleep quality, as well as several comorbidities, and the impact of EDS.